2009
DOI: 10.1111/j.1467-9450.2008.00695.x
|View full text |Cite
|
Sign up to set email alerts
|

How stable is sense of coherence? Changes following an intervention for unemployed individuals

Abstract: The present investigation was concerned with the changeability of sense of coherence. We examined changes in sense of coherence (SOC) over a six-month period in a sample of Finnish unemployed individuals (n = 74) participating in an intervention program designed to boost re-employment. Over the study period, participants' sense of coherence improved significantly and re-employed individuals reported the greatest changes. Different changes in the subcomponents of SOC, comprehensibility, manageability and meanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 53 publications
2
64
0
5
Order By: Relevance
“…No significant change of SOC scores occurred. Although other studies have demonstrated that an increase of SOC scores is possible, this requires intensive interventions focused on empowerment and development of reflection capabilities (Super et al 2015, Kähönen et al 2012, Vastamäki et al 2009). The "Healthy Slotermeer" project probably lacked that high degree of intensiveness.…”
Section: Discussion Of Main Resultsmentioning
confidence: 99%
“…No significant change of SOC scores occurred. Although other studies have demonstrated that an increase of SOC scores is possible, this requires intensive interventions focused on empowerment and development of reflection capabilities (Super et al 2015, Kähönen et al 2012, Vastamäki et al 2009). The "Healthy Slotermeer" project probably lacked that high degree of intensiveness.…”
Section: Discussion Of Main Resultsmentioning
confidence: 99%
“…However, research also pointed to the differential clinical and physiological correlates of the three SOC components and to their differential susceptibility to interventions (e.g., Bergstein, Weizman, & Solomon, 2008;Lindfors, Lundberg, & Lundberg, 2006;Vastamäki et al, 2009). Relatedly, Nio (2010) found differences between healthy adolescents and adolescents with congenital heart disease primarily on the SOC components of comprehensibility and manageability, and less so on meaningfulness.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…The experience of striving to find employment yet being unable to do so indeed is frustrating and demoralising for young adults (Vastamäki, Moser, & Paul, 2009). As such, future research should focus on more representative samples to capture the diversity of challenges with which young people are confronted.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…Interventions that provide meaning and self-efficacy in the workplace exist (Turner, Kessler, & House, 1991;Vastamäki, Moser, & Paul, 2009). Open, shared office spaces with natural lighting, for example, contribute to information sharing, to employee motivation, and to a sense of belonging to a community.…”
Section: Promoting Meaningmentioning
confidence: 99%